INOVASI KURIKULUM ENTERPRENERSHIP SEBAGAI UPAYA MEMANDIRIKAN SANTRI SECARA EKONOMI (SANTRI PREUNER) DI PESANTREN AL-ITTIFAQ BANDUNG - Chadidjah, Sitti; Basyar, Agus Samsul; Mansur, Agus Salim; Zaqiyah, Qiqi Yuliati (Universitas Islam Negeri Raden Intan Lampung, 2020)
AbstractEntrepreneurship is very important in the 4.0 era in preparing the quality Alumni of pesantren in the field of religion and entrepreneurship. So curriculum innovation in pesantren is important. This descriptive research uses a qualitative approach with the Study of Literature and case studies at Pesantren (Islamic Boarding School) Al-Ittifaq in Bandung. Based on research that Pesantren Al-Ittifaq able to produce the quality alumni in the field of religion and entrepreneurship and able to make santri independently in economic (Santripreneur). Innovations made by KH. FuadAfandi is: (1) Focus: on consumer needs (2) Totality environment: where pesantren use soil fertility as agricultural land. (3) Commitment: in carrying out the noble ideals of living for students and pesantren for the sake of Alloh’s blessing. (4) Measurement: Kiai and the students work together to expect profit (measurable), so that they can finance all needs. (5) Continuous improvement: Kiai and all students continue to improve entrepreneurship and the continuity of pesantren, so that they become independent with a turnover of billions of rupiah and a strong network of vegetable farmers.